DIGITAL ECONOMY EXTERNALITIES IN DISRUPTION OCCUPATIONAL: A CASE STUDY OF INDONESIA - Allen Pranata Putra (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTThis article will discuss externalities caused by disruption to jobs in Indonesia, furthermore the urgency of this research is to avoid the formation of negative externalities that have the potential to occur in the future. This research was conducted in 2019-2022, the focus of this article is problem shifting that has the potential to occur in all types of work while changing the economic structure that occurs in society. This research is qualitative with indepth interviews with several public officials in Indonesia. The results of this study show that market mechanisms do not form a patent pattern, so that business people cause externalities. The third point is feedback in externalities that can be interpreted that the externalities that arise are so random between positive externalities and negative externalities. The fourth point is the positive and negative of the externalities correlated in the third point, this also puts the externalities of the digital economy as an openness of data that is important to know. The fifth point is the independence of the digital economy which is based on the development of innovations for each individual who has different capabilities. Furthermore, in the sixth point, externalities occur institutionally or indivudu, in this case institutionally what is meant is comprehensive on the fundamental structure of the business. The legal method in Indonesia has the disadvantage that it cannot prevent a negative externality that harms society.Keywords: Digital Economy; Disruption; Externalities